2022
DOI: 10.1186/s13595-022-01127-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of wood harvest from sustainably managed forests in the carbon cycle

Abstract: Key message We investigate the flux balance of managed and protected forests and the effects of using wood. Flux parameters of CO2 uptake and respiration do not differ between managed and protected forests. Accounting of harvest as immediate emission by IPCC guidelines results in a bias of forest climate mitigation towards storage and neglects the avoidance of fossil-fuel use by wood use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 80 publications
0
9
0
1
Order By: Relevance
“…Forest owners tend to favour the harvesting of wood to produce forest products, while environmental groups tend to favour conservation, highlighting short‐term carbon storage effects in standing forests and improvements in biodiversity (Eriksson & Klapwijk, 2019). Continued debate surrounds the share of set‐aside forests required to ensure the protection of wildlife habitats and associated wild species (Dinerstein et al, 2019; Ellis, 2019; Roberts et al, 2020) with some studies identifying important weaknesses in arguments favouring set‐asides (Schulze, 2018; Schulze et al, 2022). Disagreements may also arise due to opposing views concerning short‐ vs. long‐term climate objectives, expectations regarding society's future dependence on carbon‐based energy and materials, and whether these needs can be met in climate‐friendly ways without using biomass (Berndes & Cowie, 2021; Cowie et al, 2021; Rodrigues et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Forest owners tend to favour the harvesting of wood to produce forest products, while environmental groups tend to favour conservation, highlighting short‐term carbon storage effects in standing forests and improvements in biodiversity (Eriksson & Klapwijk, 2019). Continued debate surrounds the share of set‐aside forests required to ensure the protection of wildlife habitats and associated wild species (Dinerstein et al, 2019; Ellis, 2019; Roberts et al, 2020) with some studies identifying important weaknesses in arguments favouring set‐asides (Schulze, 2018; Schulze et al, 2022). Disagreements may also arise due to opposing views concerning short‐ vs. long‐term climate objectives, expectations regarding society's future dependence on carbon‐based energy and materials, and whether these needs can be met in climate‐friendly ways without using biomass (Berndes & Cowie, 2021; Cowie et al, 2021; Rodrigues et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…A physiological explanation of this could be that the continuous canopy cover with a moderately high leaf area index (∼ 4 m 2 m −2 ) provide high light interception and net primary production (Bouriaud et al, under review). Regular thinning ensures that the forest has lower biomass than an undisturbed forest, and it is continuously growing, resulting in lower maintenance respiration (Schulze et al, 2022). In a different context, Bourque et al (2007) demonstrated that selection harvesting was the preferred method compared to clearcutting when the goal was to maximize total carbon storage in the forest landscape and wood products generated from harvesting over an 80-year planning horizon.…”
Section: Discussionmentioning
confidence: 99%
“…Forests ecosystems, if and when sustainably managed, offer a dual avenue for greenhouse gas (GHG) mitigation through processes that are mutually exclusive, namely sequestration and substitution (Schulze et al, 2022). Reducing harvest yields a positive impact on the forest carbon stock in the short to medium term but would adversely induce a long-term negative impact on the wood-chain value and a counterproductive effect specifically on carbon sequestration as aging trees exhibit decreased growth and carbon use efficiency (Nabuurs et al, 2013; Collalti et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…le o nazionale, è infatti un elemento fondamentale sia per la mitigazione della crisi climatica (Schulze et al 2022), sia per lo sviluppo delle economie circolari e dell'occupazione nelle zone rurali, che sono dei pilastri fondamentali del Green Deal europeo e della stessa sostenibilità globale (Biber et al 2020, Pilli et al 2022.…”
Section: Considerazioni Conclusiveunclassified